2009
DOI: 10.1097/inf.0b013e3181a06303
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Carriage of Streptococcus pneumoniae in Navajo and White Mountain Apache Children Before the Introduction of Pneumococcal Conjugate Vaccine

Abstract: The high carriage prevalence among Navajo and Apache children reflects an intense exposure to pneumococcus. The lack of modifiable risk factors for carriage highlights the importance of preventive strategies for disease control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 38 publications
5
34
1
Order By: Relevance
“…The findings in the Gaza strip are different, in that very few children attend DCC, and yet S. pneumoniae carriage was detected at a very early age. These findings are overall consistent with those obtained from other developing countries, and have been attributed to the low socioeconomic and high overcrowding conditions [12], [13], [14]. An intriguing finding in our study is the significantly lower carriage prevalence among children 6–11 months old.…”
Section: Discussionsupporting
confidence: 93%
“…The findings in the Gaza strip are different, in that very few children attend DCC, and yet S. pneumoniae carriage was detected at a very early age. These findings are overall consistent with those obtained from other developing countries, and have been attributed to the low socioeconomic and high overcrowding conditions [12], [13], [14]. An intriguing finding in our study is the significantly lower carriage prevalence among children 6–11 months old.…”
Section: Discussionsupporting
confidence: 93%
“…A small number of studies conducted outside sSA have reported a higher prevalence of carriage in males compared to females [33][35]. However, in this review gender was not associated with carriage in 9/11 studies, and in two studies carriage was more common among females [36], [37].…”
Section: Discussionmentioning
confidence: 77%
“…30 Day care attendance and young children in the household have been described as risk factors for pneumococcal colonization in American children younger than 2 years. 31 36 In Utah, the incidence of IPD due to non-PCV7 serotypes in this age group increased by 67% during 2007-2010. 13 In the current study, IPD due to non-PCV7 serotypes in young infants increased by 57% in the postvaccine introduction period, with the resultant effect being no change in the ARTICLE overall incidence of IPD in infants aged 1 to 90 days.…”
Section: Figurementioning
confidence: 99%